Islamic Studies and Smart Agriculture: Toward an Integrated Interdisciplinary Research Framework in Nigeria - Asep Suraya Maulana; Moses Adeolu AGOI; Oluwadamilola Peace AGOI; Oluwanifemi Opeyemi AGOI; Hendri Hermawan Adinugraha (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2026)
This study examines the integration of Islamic Studies with smart agriculture as an interdisciplinary approach to addressing contemporary challenges, including food insecurity, environmental degradation, and the ethical use of technology. The objective of this research is to investigate how Islamic ethical principles can inform the development, implementation, and governance of innovative agriculture technologies, ensuring sustainability and social responsibility. The method employed is a systematic literature review of scholarly publications from 2020 to 2025, drawing from agricultural science, information technology, and Islamic ethics. Core Islamic sources—including the Qur’an, Hadith, and Islamic jurisprudence (fiqh)—are analysed to identify key ethical concepts such as stewardship (khilafah), justice (‘adl), moderation (wasatiyyah), and the protection of life and resources (maqasid al-Shariah). These principles are then synthesised with current innovative agriculture practices, including the use of Internet of Things (IoT), artificial intelligence (AI), and data-driven decision-making. The results and conclusion indicate that Islamic ethical values strongly support sustainable agricultural practices, responsible data management, and equitable access to technology. However, the study also highlights ethical concerns related to automation, data ownership, and socio-economic justice. Integrating Islamic values into smart agriculture not only enhances technical efficiency but also promotes moral accountability and long-term social sustainability.